2000
DOI: 10.1023/a:1005549315846
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The role of nucleoside diphosphate (NDP) kinases in cell growth, differentiation, and tumor metastasis in relation to signal transduction was investigated. The essential role of NDP kinase in cell growth was validated by coupling between reduced NDP kinase levels, induced by antisense oligonucleotides, and the suppression of proliferative activity of a cultured cell line. In addition, because NDP kinase levels are often enhanced with development and differentiation, as has been demonstrated in postmitotic cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…Interestingly, downregulation of the expression of NM23 proteins in a rat osteosarcoma-derived cell line (UMR-106) by an antisense approach revealed that the H1 isoform is more involved in the proliferative activity than the H2 isoform (Kimura et al, 2000), a result, which is consistent with the stronger induction of this NM23 subunit by KGF and EGF and its higher expression in psoriatic skin (this study).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Interestingly, downregulation of the expression of NM23 proteins in a rat osteosarcoma-derived cell line (UMR-106) by an antisense approach revealed that the H1 isoform is more involved in the proliferative activity than the H2 isoform (Kimura et al, 2000), a result, which is consistent with the stronger induction of this NM23 subunit by KGF and EGF and its higher expression in psoriatic skin (this study).…”
Section: Discussionsupporting
confidence: 86%
“…They were originally identified as essential housekeeping enzymes required for maintenance of intracellular nucleotide concentrations. They catalyse the transfer of the g-phosphoryl group from nucleoside triphosphates to nucleoside diphosphates (reviewed in Kimura et al (2000)). In humans, eight NM23 genes have been identified: NM23-H1 to NM23-H8 (reviewed in Lacombe et al (2000)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP-5, with a match to spot 150, is the only C. elegans CYP with a predicted signal peptide. Nucleoside diphosphate kinase (NDK) (spot 157) is responsible for maintaining the levels of intracellular nucleotide pools but is also involved in cell growth, differentiation, and tumor metastasis (66). A secreted form has been found only in some bacteria (67)(68)(69) and in the nematode Trichinella spiralis (70).…”
Section: Variation In and Validation Of Vaccine Candidates Hc15 Hc24mentioning
confidence: 99%
“…The name NM (nonmetastatic) 23 was initially accorded to the matriarch of the family, NM23-H1, on the basis of its reported action as a tissue-specific metastasis inhibitor (6). Moreover, there is evidence that NM23/NDK proteins promote tumor formation and play various roles in normal development and cellular proliferation (7,8).…”
mentioning
confidence: 99%